Distribution and Characteristics of Hypouricemia within the Japanese General Population: A Cross-Sectional Study - Shin Kawasoe (Medicina, 2019)
Background and objectives: There is insufficient epidemiological knowledge of hypouricemia. In this study, we aimed to describe the distribution and characteristics of Japanese subjects with hypouricemia. Materials and Methods: Data from subjects who underwent routine health checkups from January 2001 to December 2015 were analyzed in this cross-sectional study. A total of 246,923 individuals, which included 111,117 men and 135,806 women, met the study criteria. The participants were divided into quartiles according to their serum uric acid (SUA) levels. We subdivided the subjects with hypouricemia, which was defined as SUA level ≤ 2.0 mg/dL, into two groups and compared their characteristics, including their cardiovascular risks. Results: The hypouricemia rates were 0.46% overall, 0.21% for the men and 0.66% for the women (P < 0.001). The number of the subjects with hypouricemia showed two distributions at SUA levels of 0.4–1.1 mg/dL (lower hypouricemia group), which included a peak at 0.7–0.8 mg/dL, and at SUA levels of 1.4–2.0 mg/dL (higher hypouricemia group). The men in the higher hypouricemia group had lower body mass indexes (BMI) and triglyceride (TG) levels and had higher fasting blood glucose levels than those in the lower hypouricemia group. The women in the higher hypouricemia group were younger; had lower BMI, total protein, TG, total cholesterol and low-density lipoprotein cholesterol levels; and had higher estimated glomerular filtration rates levels compared to those in the lower hypouricemia group. Conclusions: The characteristics of the individuals in the lower and higher hypouricemia groups differed significantly, indicating different pathophysiologies within each group.